Financial Reporting Quality and Sustainability Information Disclosure in Brazil - João Antônio Salvador de Souza; Leonardo Flach; José Alonso Borba; Cleber Broietti (BBR: Brazilian Business Review)
Currently, businesses face an information disclosure approach involving the triple bottom line (social, environmental, and financial). This paper aims to investigate the relationship between corporate social responsibility (CSR) information and financial reporting quality (FRQ). We argue that CSR companies behave differently in preparing financial accounting reports. Recent literature supports this theme, providing two distinct hypotheses: transparent financial reporting and retreatment. We used a sample of 1,181 companies from the years 2012 to 2016 to identify if socially responsible companies have better quality financial accounting information. In contrast to the hypotheses raised, we didn’t find a relationship between the CSR disclosures and the FRQ proxies. This suggests that sustainable companies do not explain lower or higher levels of earnings management. Our findings remain unchanged when we replace results management through discretionary accruals for manipulations of operating activities. Estimates with comparable samples also didn’t change the interpretations of the results.